Phase transition and transition kinetics of a thermotropic poly(amide-imide) derived from 70% pyromellitic dianhydride, 30% terephthaloyl chloride, and 1,3-bis[4-(4′-aminophenoxy)cumyl]benzene - Liu, S.L. (2014)
10.1021/ma010895f